Perceived service quality and customer loyalty: The mediating effect of passenger satisfaction in the Nigerian airline industry - A. Ganiyu Rahim (International Journal of Management and Economics, 2016)
The long-term survival and competiveness of the airline business is strongly connected to the quality of service offered by airline operators and their ability to satisfy and build long-term relationships with customers. This study investigates the relationship among service quality, customer satisfaction and loyalty in the Nigerian airline industry. The cross-sectional survey research design was chosen in order to collect the primary data, using a structured questionnaire. Convenience sampling was adopted to draw a sample of 800 respondents. The data collected were analysed using correlation and multiple regression analysis. The findings of this study largely support the hypothesized relationships proposed in the conceptual framework. The results specifically reveal that perceived service quality is positively related to both passengers' satisfaction and loyalty. The relationship between passenger satisfaction and loyalty towards the airlines was also found to be positive. The mediating effect of customer satisfaction between perceived service quality and customer loyalty is also found to be positive and partially supported. On the basis of the findings of this study, we conclude that perceived service quality does influence passenger satisfaction, and by extension, loyalty to the airlines. Thus, improvement of service quality is an adjuvant factor to sustainable differentiation and competitiveness in the airline industry. We therefore, recommend that airline operators develop and implement market-oriented service strategies to identify customers' needs and expectations in order to serve them better. Additionally, airline operators should measure service quality regularly to assure that they are keep meeting passengers' expectations, and consider customizing their products and services (as needed) to enhance customer satisfaction and loyalty.
Keywords: M19; Z13; 650; perceived service quality; customer loyalty; passenger satisfaction; flight experience; customer expectation; air transportation